Longer preserved urethral length in robot‐assisted radical prostatectomy significantly contributes to post‐operative urinary continence recovery. Issue 2 (12th November 2021) - Ando, Satoshi; Kamei, Jun; Yamazaki, Masahiro; Sugihara, Toru; Kameda, Tomohiro; Fujisaki, Akira; Kurokawa, Shinsuke; Takayama, Tatsuya; Fujimura, Tetsuya
Abstract: Objectives: To assess the relationship between the surgical procedure of robot‐assisted radical prostatectomy (RARP) and urinary continence recovery by reviewing the video database. Methods: Video and data about men diagnosed with prostate cancer and underwent RARP were extracted and reviewed. Preserved urethral length (PUL) was semi‐quantitatively measured using the lateral width of a 16‐Fr urethral balloon catheter while cutting the urethra on a video screen. In addition, by reviewing intraoperative RARP video database, other surgical skill outcomes were also collected. Kaplan–Meier analysis with log‐rank test was used to compare the urinary continence recovery rate, stratified by the PUL. Univariate and multivariate analyses were performed using the Cox proportional hazards model, and p ‐values of <0.05 were considered significant. Results: The number of patients included in this study was 213. In univariate analysis, a PUL of ≥16 mm, a body mass index of <23.1 kg/m 2 and a resected prostate volume of <44.3 g were statistically significant factors that influenced urinary continence recovery [hazard ratio (HR) 1.58, p = 0.036; HR 0.67, p = 0.021; and HR 0.58, p = 0.005, respectively]. Those factors also remained statistically significant in the multivariate analysis (HR 1.87, p = 0.022; HR 0.54, p = 0.001; and HR 0.57, p = 0.005, respectively). One year post‐operatively, the recovery rate from urinary continence was 79.0% for patients with a PUL of ≥16 mm and 66.5% for patients with a PUL of <16 mm. Conclusion: These results suggest that patients with longer PUL in RARP have a significantly higher rate of post‐operative urinary continence recovery.